Key factors influencing MSMEs’ adoption of DJP Online in Indonesia - Antoro, Aji Fajar Suryo; Thaha, Abdurrahman (WIM Solusi Prima, 2025)
The Directorate General of Taxes (DGT) continues to develop Direktorat Jenderal Pajak (DJP) Online as an electronic platform for the tax administration of taxpayers. It is essential to create an information technology support system that effectively improves tax collection. The purpose of this study is to analyze the factors that influence the adoption of the DJP Online system by Micro, Small and Medium Enterprises (MSMEs) using the Technology Acceptance Model (TAM) as a conceptual framework. The research method used Partial Least Squares Structural Equation Modeling (PLS-SEM) with the Smart PLS application and involved a sample of 152 MSMEs spread across South Jakarta, Bandung, and Surakarta. The results of hypothesis testing show that experience, compatibility, complexity, perceived ease of use, and perceived usefulness have different influences on the adoption of DJP Online. These factors need to be considered by DGT to increase the adoption of DJP Online. The implication of these findings is the importance of making DJP Online easier to use, compatible, and fulfilling perceived usefulness to encourage MSMEs to use this platform to increase the effectiveness and efficiency of tax administration and ultimately increase tax revenue in Indonesia.